Pengaruh Literasi dan Budaya Terhadap Keputusan Membeli Produk Halal di Kamboja - Nurul Irvin Fauziah; Riyan Pradesyah; Cut Zuriana (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This study aims to determine the effect of literacy and culture on purchasing decisions for halal products in Cambodia. This study used primary data using a questionnaire method of 150 respondents using nonprobability sampling technique. This study uses a multiple linear regression analysis model, hypothesis testing and coefficient of determination test to determine the factors that influence the buying decision of halal products in Cambodia. The results showed that the Literacy variable partially had a positive and significant effect on the Purchase Decision of halal products, the Culture variable partially had a positive and significant effect on the Purchase Decision. Simultaneously Literacy and Culture have a positive and significant effect on the Purchase Decision of halal products with a coefficient of determination of R-Square of 61.8%